Effects of electric field and heat distribution due to trends in metal stent diameter in epicardial pulsed field ablation - Zhen Wang; Ming Liang; Jingyang Sun; Jie Zhang; Yunhao Li; Daoyang Zhang; Yaling Han (Scientific Reports)
Abstract The autonomic nervous system of the heart plays a crucial role in the onset and progression of atrial fibrillation (AF). Selective ablation of the epicardial autonomic nervous system has been proposed as a potential treatment for AF. Metallic stents implanted in the epicardial fat layer of coronary arteries may undergo diameter changes due to plaque accumulation and vascular alterations. However, the impact of these changes on the electric field and temperature distribution in the ablation region remains unexplored. Two-dimensional and three-dimensional computational models were developed for the ablation region. To manage model complexity, plaque and vessels were simplified. Additionally, a 1:1 model of the ablation catheter was created to enhance data accuracy. The pulsed electric field ablation area was assessed using a field strength contour of 1000 V/cm. When the trend of metal stent diameter changes was consistent, the maximum difference in ablation area width between the two-dimensional and three-dimensional models was 0.3 mm, and the maximum temperature difference was 0.3 °C. When the trend of metal stent diameter changes was inconsistent, the maximum difference in ablation area width reached 1.95 mm, while the maximum temperature difference was 0.6 °C. Variations in metal stent diameter may have a greater impact on ablation area width. Therefore, we simulated different cross-section calculations for various models. A comparison of the two-dimensional and three-dimensional models showed that the maximum difference in ablation area width was 0.1 mm, while the maximum temperature difference was 0.5 °C. In the epicardial ablation model, variations in coronary metal stent diameter significantly impact the width of the ablation area. Considering the influence of metal stent diameter on the ablation area, the three-dimensional model provides more accurate calculations. When variations in metal stent diameter are not considered, the discrepancy between 2D and 3D model calculations is smaller. Furthermore, our study demonstrated that PFA ablation in regions with metal stents may alter the ablation effect, which has important clinical implications for the use of PFA in AF treatment.